Pengaruh Penerapan Ekonomi Hijau Terhadap Peningkatan Pendapatan Pada PT. Pertamina Geothermal Energy Tbk. - Divil Hikma Dwi Yanti; Diana Indah Sri Lestari P. A; Sunarti Sunarti; Maria Yovita R.Pandin (Universitas 45 Surabaya, 2024)
This study explores the impact of green economy implementation on revenue generation in the renewable energy sector in Indonesia, with a focus on PT Pertamina Geothernal Energy Tbk. Regression analysis shows that total electricity equivalent production has a significant effect on increasing the company's net profit, while government investment does not show a significant effect. These results suggest that increasing renewable energy production is one of the key factors in increasing revenue in this sector. The study also identified strategies to maximize the economic and environmental benefits of the transition to clean energy. These strategies include regulatory and policy reforms, effective management of public investment, and development of people- and environment-oriented policies. Implementing a green economy in Indonesia's renewable energy sector has the potential to increase revenues, promote sustainable economic growth, and preserve the environment.